An exploratory study of strategic acquisition factors relating to performance - Kusewitt, John B. (Strategic Management Journal, 1985)
Abstract This study investigated the relationship of seven common factors of acquisition strategy to the long run financial performance of acquiring firms: relative size, acquisition rate, industry commonality, timing, type of consideration, acquiree profitability and price paid. The factors were analysed individually and in concert using a database of 138 active acquiring firms which had accomplished some 3500 acquisitions during the 1967‐1976 study time period. All factors except price paid were found to be individually significantly statistically related to the performance measures. Also, these factors together accounted for most of the post‐merger financial performance which can be attributed to the acquisition programme. These results indicate that six key acquisition variables, on the average, largely determine the success of acquisition strategy. Therefore, by means of those variables, guidelines are provided that should improve the effectiveness of an acquisition programme.